An Uncommon Case of Bigamy; An Uncommon Constitutional Interpretation - Li, Nigel N. T.; Fan, Joyce C. (Columbia Journal of Asian Law, 1990)
On June 23, 1989, the Council of Grand Justices (Council) of the Republic of China (ROC) declared a Supreme Court Judgment unconstitutional for the first time in ROC history. Earlier, the Supreme Court had upheld the District Court’s nullification of a mainlander’s thirty year marriage to a Taiwanese wife on grounds of bigamy. Although the facts probably typify many cases in which spouses were separated by the 1949 split between Taiwan and mainland China, this was the first case in which the constitutional tribunal had an opportunity to review such a legal dilemma. In its review of that Supreme Court decision, the Council established a landmark precedent in ROC constitutional jurisprudence that significantly impacts not only the substantive law, but also the procedural law of the ROC.